Soybean genomics research community strategic plan: A vision for 2024–2028 - Robert M. Stupar; Anna M. Locke; Doug K. Allen; Minviluz G. Stacey; Jianxin Ma; Jackie Weiss; Rex T. Nelson; Matthew E. Hudson; Trupti Joshi; Zenglu Li; Qijian Song; Joseph R. Jedlicka; et al. (The Plant Genome)
Abstract This strategic plan summarizes the major accomplishments achieved in the last quinquennial by the soybean [Glycine max (L.) Merr.] genetics and genomics research community and outlines key priorities for the next 5 years (2024–2028). This work is the result of deliberations among over 50 soybean researchers during a 2‐day workshop in St Louis, MO, USA, at the end of 2022. The plan is divided into seven traditional areas/disciplines: Breeding, Biotic Interactions, Physiology and Abiotic Stress, Functional Genomics, Biotechnology, Genomic Resources and Datasets, and Computational Resources. One additional section was added, Training the Next Generation of Soybean Researchers, when it was identified as a pressing issue during the workshop. This installment of the soybean genomics strategic plan provides a snapshot of recent progress while looking at future goals that will improve resources and enable innovation among the community of basic and applied soybean researchers. We hope that this work will inform our community and increase support for soybean research.